PENGARUH INVESTASI ASING DAN NET EKSPOR NON MIGAS TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI KALIMANTAN TIMUR TAHUN 2009.I-2016.IV - Nirwana Sangga Langi; Aris Soelistyo (Jurnal Ilmu Ekonomi JIE, 2019)
Economic growth is one of the important indicators to know how big the success of regional development and as a determinant of future development policy. Some experts say that export and investment was the "engine of growth". This study aims to determine the effect of foreign investment and non-oil exports net on economic growth in both short and long term. This research used quarterly data from 2009.I to 2016.IV.During the observation, the researcher utilizes Partial Adjusment Model method. The results shows that the influences between economic growth with foreign investment (PMA) in the short term is 0.12% and in the long term is 0.27%.While in the short term, the influence between economic growth with non-oil exports net is 0.03% and in the long term is 0.07%. Keywords: Economic growth, foreign investment, non-oil exports net, PAM